Judges' Ratio Decidendi in Marriage Dispensation Cases at The Gresik Religious Court Regarding Marriage Age Limit - Murniati, Dewi (Universitas Wijaya Kusuma Surabaya, 2020)
This study discusses the Marriage Age Limit Provisions According to Law Number 1 of 1974 concerning Marriage (Case Study in the Gresik Religious Court), this research is based on the number of divorce cases in the Gresik Religious Court, which are still dominated by productive age, Seeing the phenomenon, those who generally immature, not adequately prepared to enter the world of marriage, the marriage dispensation granted in a religious court on the lives of those who are married has both positive and negative effects. The positive impact of preventing adultery is that the opposing side is prone to disputes because those relatively young certainly have different thoughts from those who have grown up. This study examines and analyses the age limit's application for marriage and analyses the judges' considerations in examining and determining marital dispensation cases in the Gresik Religious Court. To answer the problem, the writer uses socio-legal research methods. The data used were sourced from legislation, literature study, and scholars' opinions and data obtained from the Gresik Religious Court. The study results show that applying the age limit for marriage is less practical or cannot be fully used to the people in the Gresik Religious Court's jurisdiction. This is indicated by the high number of marriage dispensation requests in the Gresik Religious Court. Secondly, the Judge's consideration in examining the case for a marriage dispensation request at the Gresik Religious Court was under the procedures set out in Perma Number 5/2019. Keywords: Marriage, Dispensation, Age